Perspektif Pengalaman Guru Dalam Berkomunikasi Secara Efektif Dalam Melakukan Proses Pembelajaran Terhadap Anak Usia Dini Di Tk An Nizam Islamic School - Nover Bintang Siahaan; Rawaty O F Panggabean; Rachel Theresia Natanael Tambun; Elya Siska Anggraini; Aman Simaremare (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Effective communication between teachers and students is an important key in improving learning outcomes and student motivation, especially at an early age. This research aims to find out what teachers' experiences are in carrying out effective educational communication with young children. The research method used was descriptive qualitative by conducting interviews with one of the Kindergarten teachers at An Nizam Islamic School Medan who had good communication when teaching early childhood. The research results show that teachers who are effective in educational communication have the ability to use various communication strategies, such as using simple and clear language, using images and symbols, and providing constructive feedback. Apart from that, teachers must also have the ability to understand students' needs and interests, and be aware of the importance of effective communication in improving learning outcomes. In synthesis, this research shows that the teacher's ability to carry out effective educational communication is very important in improving learning outcomes and motivation of early childhood (AUD).